2014
DOI: 10.1007/s00787-014-0629-5
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents in secure residential care: the role of active and passive coping on general well-being and self-esteem

Abstract: Coping, general well-being and self-esteem play an important role during the process of adaptation to turning points in life-course. This study aimed to investigate the effect of coping on both the development of general well-being and self-esteem of adolescents with severe psychiatric problems in secure residential care. In addition, risk and protective factors were taken into account. Adolescents between the age of 16 and 18 (N = 172) were followed for 1.5 years. General well-being and self-esteem were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 35 publications
1
29
0
1
Order By: Relevance
“…This could be an important alternative target for intervention in addition to psychiatric health services and trauma therapy whenever indicated. Barendregt et al showed that the use of active coping strategies was associated with increase in self-esteem in their longitudinal study of adolescents with severe psychiatric problems in secure residential care (Barendregt, Van der Laan, Bongers, & Van Nieuwenhuizen, 2015). Enhancing active coping strategies could therefore be one way of achieving higher self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…This could be an important alternative target for intervention in addition to psychiatric health services and trauma therapy whenever indicated. Barendregt et al showed that the use of active coping strategies was associated with increase in self-esteem in their longitudinal study of adolescents with severe psychiatric problems in secure residential care (Barendregt, Van der Laan, Bongers, & Van Nieuwenhuizen, 2015). Enhancing active coping strategies could therefore be one way of achieving higher self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these examples, it is hardly surprising that reviews on the concepts of resilience or well-being have 2 "Resilience. The capacity to cope with adversity and to avoid breakdown when confronted by stressors differs tremendously among individuals.…”
mentioning
confidence: 99%
“…1). However, while frequently debated, the number of papers directly addressing these two concepts (indicated by their appearance in title and/or abstract) is far lower, with only six papers [1][2][3][4][5][6] carrying either term in their title (Fig. 1).…”
mentioning
confidence: 99%
“…Individuals who react and deal with their problems in different ways have varying well-being outcomes. Those who employ active coping strategies, such as seeking social support, have a higher level of self-esteem while those who use passive coping styles, such as avoiding problems, are more prone to experience low general well-being [53].…”
Section: Predictors Of Well-beingmentioning
confidence: 99%